Kepribadian Seorang Pendidik Di Tinjau Dari Perspektif Hadits - Siti Nurrahmah, Mahallia; Ferianto, Ferianto (Wahana Karya Ilmiah Pendidikan, 2023)
Personality competence is an element that forms human character. A good personality will certainly reflect good character. When implemented in the world of education, personality that makes the teacher a real figure in providing an example to his students. It is often said that teachers are figures who should be respected and emulated in all their behavior and actions. With education, human status will be raised, namely people who are knowledgeable. Education contains knowledge that is very important for humanity. competence has a big influence on the behavior shown by a teacher. Behavior dance with the concept of Knowledgeable people can always learn lessons from events that occur, experience, or come to them in life. Those who are knowledgeable are always enthusiastic about pursuing knowledge so that they have the ability to see deeper into the causes and effects of something. It is explained in a hadith that the superiority of an alim over an abid is like my superiority Angels and the inhabitants of the heavens and the earth, even the ants in their nests up to the whales, they will pray for people who teach kindness to human.